Investigation of an algae-derived polymer as a pollinator-friendly pesticide adjuvant - Narayanan Kannan; Yu-Cheng Zhu (Scientific Reports)
Abstract Chemical applications in croplands can be a major source of pesticide exposure to pollinators, including off-target drift. Adjuvants are added to pesticides to improve spray characteristics. The major goal of this study was to identify the possibility of using sodium alginate (SA) as a drift-reducing pesticide adjuvant that is less/nontoxic to honeybees than polyacrylamide (PAM) an industry standard. The toxicity bioassay experiments were carried out with six- to eight-day-old, caged honeybee workers. Each cage contained 20 honeybees. Caged bees were treated with adjuvant, insecticide, adjuvant + insecticide, and a water only as a control, using a modified Potter Spray Tower. The insecticides imidacloprid and bifenthrin were used at three different concentrations (LC25, LC50, and LC75). Two different concentrations of the adjuvants SA and PAM were tested. The 48-hour mortality results were recorded. Our results indicate noticeable reductions in bee killing when SA is used as an insecticide adjuvant instead of PAM.